Documents of the authorities of Moscow diocese on penitential prayers in the territory of Moscow on the occasion of national disasters in 1919 - Andrey Borisyuk (Вестник Православного Свято-Тихоновского гуманитарного университета: Серия ИИ. История, история Русской Православной Церкви)
The publication presents documents of the Moscow Diocesan authorities related to the organization of national penitential events in 1919: the Message of Archbishop Joasaph (Kallistov) on the need for repentance from August 2, 1919, the Decree of the Moscow Diocesan Council on penitential services, Appendices to the decree: permanent additions to the services (litanies and penitential prayer), the Brochure "Repentance is the need of our time". These documents appeared as a reaction of the diocesan authorities to the nationwide disasters that occurred after the revolution (poverty, famine, epidemics) and were sent to the churches of the Moscow Diocese. They contain both practical instructions of a liturgical nature and a theoretical understanding of the events taking place from a theological point of view. The hardships of the time experienced are perceived in these sources as the result of a sin that requires repentance. The idea is substantiated that without the elimination of the spiritual causes of disasters, any other struggle against them will not be successful. The need to organize special church penitential events was noted by the supreme Ecclesiastical authority (represented by the Patriarch), and was also the most important activity of the Moscow Diocesan Council in 1919, while to this day this activity remains practically unexplored. The documents presented in this article are published for the first time.